Computational studies of the role of serotonin in the basal ganglia - Best, Janet; Reed, Michael C.; Nijhout, H. F. (Frontiers in Integrative Neuroscience, 2013)
It has been well established that serotonin (5-HT) plays an important role in the striatum. For example, during levodopa therapy for Parkinson’s disease (PD), the serotonergic projections from the dorsal raphe nucleus release dopamine as a false transmitter, and there are strong indications that this pulsatile release is connected to dyskinesias that reduce the effectiveness of the therapy. Here we present hypotheses about the functional role of 5-HT in the normal striatum and present computational studies showing the feasibility of these hypotheses. Dopaminergic projections to the striatum inhibit the medium spiny neurons (MSN) in the striatopalladal (indirect) pathway and excite MSNs in the striatonigral (direct) pathway. It has long been hypothesized that effect of dopamine (DA) depletion caused by the loss of SNc cells in PD is to change the “balance” between the pathways to favor the indirect pathway. Originally, “balance” was understood to mean equal firing rates, but now it is understood that the level of DA affects the patterns of firing too. There are dense 5-HT projections to the striatum from the dorsal raphe nucleus and it is known that increased 5-HT in the striatum facilitates DA release from DA terminals. The direct pathway excites various cortical nuclei and some of these nuclei send inhibitory projections to the DRN. Our hypothesis is that this feedback circuit from the striatum to the cortex to the DRN to the striatum stabilizes the balance between the direct and indirect pathways, and this is confirmed by our model calculations. Our calculations also show that this circuit contributes to the stability of the dopamine concentration in the striatum as SNc cells die during Parkinson’s disease progression (until late phase). There may be situations in which there are physiological reasons to “unbalance” the direct and indirect pathways, and we show that projections to the DRN from the cortex or other brain regions could accomplish this task.